Upaya Peningkatan Partisipasi Masyarakat Dalam Pembangunan Daerah (Studi Pada Lingkungan Kelurahan Mandaranrejo, Kecamatan Bugulkidul, Kota Pasuruan) - Maulana Oktarian Faizal (Jurnal Administrasi Publik, 2013)
Abstract: Efforts to Increase Society Participation in Regional Development at Mandaranrejo. This study  aims  to determine how public participation in development in Kelurahan Mandaranrejo. This research using a qualitative approach. As a  result  of the discussion can be concluded that public participation in regional development is needed to make the development done in accordance with the needs of the public so that the development to be right on target. The participation as stated in the form of an idea, then become a development plan. The role of Government is crucial in the implementation of development as community coordinator who delivered plans and development purposes as well as to urge people to participate in development. Therefore the government should use the communication media comprehensible by the whole society of Kelurahan Mandaranrejo caused by they having different educational background. The government also should provide motivation to society by establishing good relations with communities to improve participation in regional development. Resources of the government apparatus should have the ability to develop a way of communicating with the public in order for the communication that is done can be more effective. The existence of the government apparatus resources are insufficient then can be created innovations in a communication that is expected to improve public participation in regional development. Keywords: Development, Participation, Communication Abstrak: Upaya Peningkatan Partisipasi Masyarakat Dalam Pembangunan Daerah Di Kelurahan Mandaranrejo. Penelitian ini bertujuan untuk mengetahui bagaimana partisipasi masyarakat pada pembangunan daerah di Kelurahan Mandaranrejo. Penelitian ini menggunakan pendekatan kualitatif. Dari pembahasan dapat disimpulkan bahwa pembangunan daerah harus disesuaikan dengan kebutuhan masyarakat agar pembangunan tersebut tepat sasaran. Partisipasi dapat diwujudkan dalam bentuk gagasan masyarakat yang kemudian dijadikan sebagai rencana pembangunan. Peran Pemerintah sangat penting sebagai koordinator masyarakat yang menyampaikan rencana pembangunan serta mengajak masyarakat turut berpartisipasi dalam pambagunan daerah. Maka dari itu, pemerintah hendaknya menggunakan media komunikasi yang mudah dipahami oleh seluruh lapisan masyarakat yang disebabkan perbedaan latar belakang pendidikan. Pemerintah juga harus memberikan motivasi dengan menjaga hubungan baik dengan masyarakat. Aparat pemerintah harus mempunyai kemampuan untuk berkomunikasi dan menciptakan inovasi dalam berkomunikasi dengan masyarakat yang akhirnya berdampak pada peningkatan partisipasi masyarakat dalam pembangunan daerah.   Kata Kunci: Pembangunan, Partisipasi, Komunikasi